Reimagining the "America" in American Catholicism - Portier, William L. (Horizons, 2017)
Your faces bring back memories of thirty-six previous CTS convention banquets. The first was in 1979. It was held at Trinity College in Washington. I was a graduate student. Bill Cenkner was president. I'm here tonight, warts and all, where Bill stood in 1979. I think of Gerry Sloyan, Vera Chester, Dolores Greeley, Mary Lea Schneider, and the rest. To a much younger me they loomed larger than life. Tonight I want to thank you for the honor of serving briefly with them in the long line of our society's presidents. And a special thanks to my family, who made the trip to Newport to be here with us tonight.